2023
DOI: 10.1039/d2tb01977a
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm mechanisms of carbon dots: a review

Abstract: Due to the increasing bacterial resistance to conventional antibiotics, developing a safe and effective methods to combat infections caused by bacteria and biofilms has become an urgent clinical problem. Recently,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 112 publications
(168 reference statements)
0
28
0
Order By: Relevance
“…This is majorly due to the production of ROS, which induces oxidative stress in bacteria, disrupting the integrity of cell membranes and leading to cell death. 34 Researchers can regulate the level of ROS in bacteria and introduce environment-responsive mechanisms, which may improve the performance of CDs and bring smart anti-bacterial functions.…”
Section: Resultsmentioning
confidence: 99%
“…This is majorly due to the production of ROS, which induces oxidative stress in bacteria, disrupting the integrity of cell membranes and leading to cell death. 34 Researchers can regulate the level of ROS in bacteria and introduce environment-responsive mechanisms, which may improve the performance of CDs and bring smart anti-bacterial functions.…”
Section: Resultsmentioning
confidence: 99%
“…The main antibacterial and antibiofilm mechanisms of CDs are mainly the effect of positive surface charge, the effect of hydrophobic interactions, the effect of particle morphology and size, oxidative damage, photothermal effects, the effect on the structure and function of DNA and RNA, the effect on the activity of proteins, the retention of the active structure of drug molecules, hampering the adhesion process, inhibition of quorum sensing, inhibition of biofilm formation by killing bacteria, and elimination of mature established biofilm. 16 Based on the retention principle of active structures, Ch-CDs not only inherit the aforementioned antibacterial and antibiofilm mechanisms of conventional carbon dots but also develop highly selective activity as antibacterial agents because their chiral and tunable optical properties enable them to selectively label and target bacterial cells. 102 In recent years, targeting Ch-CDs in the context of antibacterial compounds has improved selectivity by exploiting differences in binding affinity between target bacterial cells and host cells.…”
Section: Drug Carriersmentioning
confidence: 99%
“…Carbon dots (CDs), a novel zero-dimensional carbon nanomaterial, have been widely used in chemical and biological sensors, − cellular and biological imaging, − drug delivery, − and antimicrobial therapy − for their chemical stability, excellent optical properties, outstanding biocompatibility, and antibacterial ability , since their first discovery in 2004 . With continuous in-depth research in the field of CDs, researchers found that some CDs synthesized with chiral precursors retained the chirality of the precursor, and the concept of chiral carbon dots (Ch-CDs) was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, its applicability in biomedical applications shows great promise due to its chemical inertness, extensive π-conjugation system, outstanding biocompatibility, and low toxicity . One of the key factors contributing to GQD’s remarkable antibacterial behavior lies in its Gaussian surface, which facilitates effective interaction with bacterial surfaces, ultimately disrupting bacterial cells and enhancing its antimicrobial efficacy . Additionally, the photoexcitation behavior of GQD induces the generation of reactive oxygen species (ROS), which strengthens its capacity to destroy bacterial cells .…”
Section: Introductionmentioning
confidence: 99%
“…6 One of the key factors contributing to GQD's remarkable antibacterial behavior lies in its Gaussian surface, which facilitates effective interaction with bacterial surfaces, ultimately disrupting bacterial cells and enhancing its antimicrobial efficacy. 7 Additionally, the photoexcitation behavior of GQD induces the generation of reactive oxygen species (ROS), which strengthens its capacity to destroy bacterial cells. 8 This remarkable antibacterial behavior has led to the commercial utilization of GQD in bandages and dressing materials for wound disinfection and healing.…”
Section: ■ Introductionmentioning
confidence: 99%